URGENSI PENERAPAN PENDEKATAN PEMBELAJARAN KONTEKSTUAL PADA SEKOLAH TINGKAT DASAR - Azhar, Imam (Journal Of Islamic Elementary School (JIES), 2021)
Contextual teaching and learning is a conception of teaching and learning that helps teachers relate subject matter content to real world situations; and motivates students to make connections between knowledge and its applications to their lives as family members, citizens, and workers and engage in the hard work that learning requires. Thus, CTL helps students connect the content they are learning to the life contexts in which that content could be used. Students then find meaning in the learning process. As they strive to attain learning goals, they draw upon their previous experiences and build upon existing knowledge. There are sevent components in CTL; constructivism, inquiry, questioning, modelling, learning community, reflection, and authenthic assessment. When the teachers implemented CTL, they should take into action about REACT or relating, experiencing, applying, cooperating, dan transfering. Such plans are based on CTL principles and approaches that require teachers to serve in the following roles: facilitator, organizer of the teaching/learning/ assessment process, role model, learning mentor, and content specialist. Although the teacher can implement CTL individually, teacher collaboration maximizes interdisciplinary learning.